2011
DOI: 10.1515/hc.2011.025
|View full text |Cite
|
Sign up to set email alerts
|

Recyclization reactions of 1-alkylpyrimidinium salts

Abstract: The reaction of 4-amino-2-benzyl-1-methyl-5-ethoxycarbonylpyrimidinium iodide (3) with alcoholic methylamine resulted in the formation of the methylimine of 2-amino-4-hydroxy-6-methylamino-5-phenylpyridine-3-carbaldehyde (5). Heating of the same pyrimidinium salt in benzylamine gave a mixture of products of two C–C recyclizations: 2-benzyl-4-benzylamino-5-carbamoylpyrimidine (7) and the benzylimine of 4-amino-2-benzyl-6-benzylaminopyrimidine-5-carbaldehyde (8). The reaction of 2-amino-1,4-dimethyl-5-ethoxycarb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…This ring cyclization reported to have a rate limiting step and there are few homogeneous and heterogeneous catalysts reported for the same. Though these catalysts often result in improved yields [22,23], cost of the catalyst, difficulty in isolation, presence of traces by catalyst in final product etc., prohibit their use in bulk drug or medicinal chemistry synthesis [24][25][26][27]. The nanomaterial based catalysis is not reported for pyrimidine synthesis and our group has recently reported that Fe 3 O 4 @SiO 2 acts as an inert support in some organic reactions.…”
Section: Introductionmentioning
confidence: 99%
“…This ring cyclization reported to have a rate limiting step and there are few homogeneous and heterogeneous catalysts reported for the same. Though these catalysts often result in improved yields [22,23], cost of the catalyst, difficulty in isolation, presence of traces by catalyst in final product etc., prohibit their use in bulk drug or medicinal chemistry synthesis [24][25][26][27]. The nanomaterial based catalysis is not reported for pyrimidine synthesis and our group has recently reported that Fe 3 O 4 @SiO 2 acts as an inert support in some organic reactions.…”
Section: Introductionmentioning
confidence: 99%